2020
DOI: 10.3389/fnins.2020.491478
|View full text |Cite
|
Sign up to set email alerts
|

Lesion Induced Error on Automated Measures of Brain Volume: Data From a Pediatric Traumatic Brain Injury Cohort

Abstract: Structural segmentation of T1-weighted (T1w) MRI has shown morphometric differences, both compared to controls and longitudinally, following a traumatic brain injury (TBI). While many patients with TBI present with abnormalities on structural MRI images, most neuroimaging software packages have not been systematically evaluated for accuracy in the presence of these pathology-related MRI abnormalities. The current study aimed to assess whether acute MRI lesions (MRI acquired 7–71 days post-injury) cause error i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…However, it is possible that similar errors of varying magnitude are present in other studies in which changes in the rates and location of tissue misclassification can produce artifactual findings. Identifying more reliable data acquisition and processing methods that improve or better leverage tissue contrast, and therefore reduce the reliance on spatial tissue probability priors, may also improve segmentation performance in volumetric analyses of the brain in the presence of atrophy [ 31 ], unique morphology [ 60 , 61 ], or normal development [ 62 ], in which salient changes in brain and/or CSF volumes may interact with the positioning of the cortex with respect to other tissues and produce a spatial bias in segmentation errors between conditions of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that similar errors of varying magnitude are present in other studies in which changes in the rates and location of tissue misclassification can produce artifactual findings. Identifying more reliable data acquisition and processing methods that improve or better leverage tissue contrast, and therefore reduce the reliance on spatial tissue probability priors, may also improve segmentation performance in volumetric analyses of the brain in the presence of atrophy [ 31 ], unique morphology [ 60 , 61 ], or normal development [ 62 ], in which salient changes in brain and/or CSF volumes may interact with the positioning of the cortex with respect to other tissues and produce a spatial bias in segmentation errors between conditions of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for our unexpected finding (i.e., decreased CSF volume in children with an mTBI) is lesion-induced errors in the volumetric results. Prior research with pediatric populations and TBI have found biases in automated software packages (e.g., Freesurfer pipelines) that can be attributed to lesions (62). Methods that incorporate a focal pre-processing approach (e.g., enantiomorphic filling of the damaged area) can reduce errors and improve the detection of physiologically meaningful differences (62, 63).…”
Section: Discussionmentioning
confidence: 99%
“…The present study introduces personalized measurement and analysis of individual connectomic profiles in five chronic moderate-to-severe TBI patients with varying lesion loads, mechanisms of injury, age at injury, and burden of neural/cognitive symptoms. Our implementation extends current methods by addressing the long-standing and prominent challenge of analysing TBI structural profiles when automatic sub/cortical segmentation or parcellation of MRIs fail in the presence of lesions 18 . Significantly, this problem is addressed here by synergizing connectomic analysis with virtual brain repair , where the lesion is replaced by healthy looking tissue in the T1-weighted images (lesion inpainting).…”
mentioning
confidence: 99%
“…(which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. moderate to severe TBI cohorts with diverse brain injuries pose a serious technical challenge, as the available tools for MRI processing to generate connectomes fail in such 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation